2017
DOI: 10.1097/j.pain.0000000000001021
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin-dependent kinase 5 modulates the P2X2a receptor channel gating through phosphorylation of C-terminal threonine 372

Abstract: The purinergic P2X2 receptor (P2X2R) is an ATP-gated ion channel widely expressed in the nervous system. Here, we identified a putative Cdk5 phosphorylation site in the full-size variant P2X2aR (372TPKH375), which is absent in the splice variant P2X2bR. We therefore investigated the effects of Cdk5 and its neuronal activator, p35, on P2X2aR function. We found an interaction between P2X2aR and Cdk5/p35 by co-immunofluorescence and co-immunoprecipitation in HEK293 cells. We also found that threonine-phosphorylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 62 publications
1
19
0
Order By: Relevance
“…HEK293 cells (ATCC#CRL-1573) were grown in Dulbecco Modified Eagle Medium (DMEM) containing 10% of fetal bovine serum (FBS) and penicillin/streptomycin (100 mg/mL) (Invitrogen, Carlsbad CA). HEK293 cells were transiently co-transfected with mouse CMV-p35 (Coddou et al, 2017 ) and HyPer constructs (Evrogen, Moscow, Russia) by using Lipofectamine 2000 reagent (Invitrogen, Carlsbad CA) and treated with roscovitine (30 μM, Sigma-Aldrich, Saint Louis, MO) or VAS2870 (1 μM, Calbiochem, CA USA) during 24 h and 1 h, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…HEK293 cells (ATCC#CRL-1573) were grown in Dulbecco Modified Eagle Medium (DMEM) containing 10% of fetal bovine serum (FBS) and penicillin/streptomycin (100 mg/mL) (Invitrogen, Carlsbad CA). HEK293 cells were transiently co-transfected with mouse CMV-p35 (Coddou et al, 2017 ) and HyPer constructs (Evrogen, Moscow, Russia) by using Lipofectamine 2000 reagent (Invitrogen, Carlsbad CA) and treated with roscovitine (30 μM, Sigma-Aldrich, Saint Louis, MO) or VAS2870 (1 μM, Calbiochem, CA USA) during 24 h and 1 h, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Cdk5 is an essential kinase in brain development and function (Dhariwala and Rajadhyaksha, 2008 ; Utreras et al, 2009a ; Contreras-Vallejos et al, 2012 ). Interestingly, our group reported earlier that Cdk5 plays a crucial role during inflammatory pain signaling (Utreras et al, 2009a , 2011 ; Prochazkova et al, 2013 ; Rozas et al, 2016 ; Coddou et al, 2017 ). Cdk5 is a proline-directed serine/threonine kinase, mostly active in post-mitotic neurons, where its specific activators p35 and p39 are mainly expressed (Lew et al, 1994 ; Dhariwala and Rajadhyaksha, 2008 ; Utreras et al, 2009c ).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Unlike the activation of other Cdks, the activation of Cdk5 requires the binding of its own specific partners, p35 and p39 (Pareek and Kulkarni ), especially p35, which is more capable of binding and activating Cdk5 than p39 (Utreras et al ). Increasing evidence has shown that Cdk5 activation may be involved in pathological pain conditions (Jendryke et al ; Coddou et al ; Moutal et al ) and contribute to neurodegeneration (Yousuf et al ). Administration of the Cdk5/p35 inhibitor roscovitine alleviates neuropathic pain (Yang et al ), inflammation‐induced pain (Zhang et al ) and cancer‐induced pain (Zhang et al ), implying that the activation of Cdk5 is critical for the formation of pain.…”
Section: Introductionmentioning
confidence: 99%